EP524 The significance of positive peritoneal cytology in G1/G2 endometrioid carcinoma of uterine body. (1st November 2019) - Furukawa, S; Iwase, H; Endo, S; Ohnishi, K; Tazo, Y; Takada, T; Arai, M; Yoshino, O; Onda, T
Abstract : Introduction/Background: Although peritoneal cytology in endometrial carcinoma was excluded from the staging system (FIGO 2008), the management for patients with positive peritoneal cytology remains controversial. The aim of this study is to evaluate the clinical significance of positive peritoneal cytology in G1/G2 endometrioid carcinoma. Methodology: We retrospectively reviewed medical records of 365 patients with G1/G2 endometrioid carcinoma who were primarily treated at our hospital from 2005 to 2013. We analyzed clinicopathological features and prognosis of patients with positive (P group, N=45) and negative (N group, N=320) peritoneal cytology. Fisher's exact test, Kaplan-Meier analysis, and Log-rank test were used for statistical analyses. Results: Median age of all patients was 56 years-old (range 27–83), and stage distribution was 290/25/47/3 in stage I/II/III/IV (FIGO 2008). Median follow-up period was 61 months (range 1–130). The frequency of metastasis to adnexa, lymph nodes (LN), and distant organs was significantly high in P group compared with N group ( p =0.0002, 0.0034, 0.0018, respectively). However, omental metastasis was not related with the results of cytology. The number of patients in low, intermediate, and high risk for recurrence defined in Japanese guidelines for treatment of uterine body neoplasm was 20/6/19 in P group and 202/62/56 in N group. Forty of 45 patients (89%) in P group received adjuvant treatment, while 110/320 (34%) in N group. Overall survival (OS) in P group was significantly poor compared with N group in patients with high risk for recurrence (75.0% vs 88.4% in 5-year OS, p=0.0067), although there was no difference in patients with both low and intermediate risks. Conclusion: As the frequency of lymph node metastasis is significantly high, appropriate evaluation of lymph node metastasis is necessary in P group. Further, more effective adjuvant treatment is desirable for patients with high risk in P group to improve the prognosis. Disclosure: Nothing to disclose.